Total war: resistance, humanitarian aid and media - Petras, James (2003)
In all likelihood the post-war period will see humanitarian aid being used to legitimate `transatlantic solidarity' and US colonial rule. Effective humanitarian aid would include contributions from the UN in addition to the oil-for-food programme and would be delivered to people through organisations like the Red Crescent and other civil society groups. - Reproduced.
Keywords: War; United States - Foreign relations - Iraq; International relations